'Eco-Hauling' principles to reduce carbon emissions and the costs of earthmoving - A case study. (20th January 2019) - Krantz, Jan; Feng, Kailun; Larsson, Johan; Olofsson, Thomas
Abstract: Mitigating emissions of carbon dioxide and other greenhouse gases is critical if we are to meet the increasing threats posed by global warming. Previous studies have shown conclusively that a substantial part of all carbon dioxide emissions comes from transportation, and that Eco-Driving principles based upon strategic, tactical, and operational decisions have the potential to reduce these emissions. However, these well-established principles have been neglected within the construction industry despite the large number of transport-related activities that attend most construction projects. This paper therefore aims to increase awareness and understanding within the industry of the potential reductions of both carbon dioxide emissions and the costs of earthmoving activities that could be achieved through the use of Eco-Driving principles. A new concept labeled 'Eco-Hauling', which extends the Eco-Driving concept to earthmoving, is proposed. A case study of a road project has been conducted and used to demonstrate the new concept. Discrete-event simulation is used to support the data analysis as it enables modeling of the dynamic interactions between equipment and activities of multiple different construction scenarios. The presented findings show that a combination of decisions taken from the proposed Eco-Hauling concept can enable earthmoving contractors to substantially reduce carbon dioxide emissions and costs while maintaining productivity. This study has implications for the general advancement of Eco-Driving theory, as well as for project management as it sets out a viable approach for reducing greenhouse gas emissions in construction projects. Highlights: The Eco-Hauling concept is proposed by extending Eco-Driving to earthmoving. The concept was demonstrated in a case study using discrete-event simulation. A multi objective trade-off determines the optimal Eco-Hauling scenarios. The reduction potential was shown at 6.94% in CO2 emissions and 15.63% in costs.